The student life handbook - Fanthome, Christine (Palgrave study guides, 2005)
Many students arrive at university with the idea that this will be 'the time of their lives'. Covering many aspects of university life such as finance, accommodation, leaving home and joining the social scene, this guide will help students reap the greatest possible benefit and enjoyment from their time at university